A composite mineral material for removing manganese from acid mine drainage and a method for preparing the same
Patent Information
- Application Number
- CN202611016537.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-09
AI Technical Summary
但即便如此,单一方解石体系经活化后其界面结构仍显单一,Mn(II)沉淀产物依旧集中沉积于有限的表面活性位点,表面钝化引发的活性衰减问题未能得到根本改善
1.本发明通过方解石与镁橄榄石的共磨活化,在酸性条件下(初始pH 2.0~4.0)对Mn(II)的去除率可达79%~92%以上,投加量仅需0.1~2.0 g/L,反应时间1~3 h即可完成处理;相比现有技术中单独球磨方解石或简单物理混合物,去除率提升了1.7~4.0倍,且适用于酸性矿山废水组合处理工艺中的后段深度除锰单元,工程适应性好。
Smart Images

Figure CN122877880A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of mine wastewater treatment technology, and more specifically, to a composite mineral material for removing manganese from acidic mine wastewater and its preparation method. Background Technology
[0002] Acid mine wastewater (AMD) is mainly formed by the oxidation of metal sulfides (such as pyrite) under the synergistic action of air, water, and microorganisms. It is generally characterized by low pH, high sulfate concentration, and the coexistence of multiple heavy metal ions. Among these, Mn(II) exhibits high solubility and strong migration under acidic conditions, and its homogeneous oxidation kinetics are slow, making it considered one of the most difficult pollutants to remove effectively in AMD. Mn(II) readily migrates and spreads continuously in the aquatic environment of mining areas, posing a long-term environmental risk to the receiving aquatic ecosystem.
[0003] For the treatment of Mn(II) in AMD, the following technical approaches are currently mainly used: Neutralization precipitation method uses alkaline materials such as lime and limestone to raise the pH of wastewater, causing Mn(II) to precipitate in the form of hydroxides or carbonates. However, this method has limited removal efficiency for Mn(II), and usually requires the pH to be raised to above 9.0 to achieve effective precipitation. It also consumes a large amount of reagents and generates a large amount of manganese-containing sludge. Oxidation precipitation method converts Mn(II) into insoluble MnO2 through aeration or the addition of strong oxidants. However, the oxidation rate is extremely low under low pH conditions, and a relatively high pH needs to be maintained in actual operation, resulting in high energy consumption and reagent costs, which limits its engineering application. Adsorption method uses adsorbents such as activated carbon, zeolite, and biomass to remove Mn(II), but the adsorption capacity is generally limited, adsorbent regeneration is difficult, and the economics of industrial application are poor. Calcite mineral treatment method has good application prospects in the field of AMD neutralization and heavy metal removal because calcite (CaCO3) is widely available, inexpensive, and environmentally compatible. However, natural calcite has a dense crystal structure and limited specific surface area, resulting in insufficient solubility and interfacial reactivity. Furthermore, when treating high-manganese acidic wastewater, a dense manganese-containing deposition layer (such as MnCO3, MnO) gradually forms on the surface of the calcite. x This capping layer forms a diffusion barrier, which severely inhibits the continuous dissolution of minerals and the interfacial mass transfer process, exhibiting significant surface passivation and self-inhibition characteristics, ultimately leading to a significant decrease in the Mn(II) removal capacity.
[0004] In recent years, mechanoactivation technology has attracted attention in the field of environmental mineral materials, effectively enhancing mineral reactivity through particle refinement, structural disordering, and increased active sites. Studies have shown that mechanoactivation can significantly increase the dissolution rate of calcite and Ca2+. 2+Release capacity. However, even so, the interface structure of the single calcite system remains relatively simple after activation, and Mn(II) precipitates are still concentrated on a limited number of surface active sites, failing to fundamentally improve the activity decay problem caused by surface passivation. Meanwhile, existing research mainly focuses on the removal of easily precipitated heavy metals such as Cu, Pb, Cd, and Zn by calcite, while there is a lack of targeted material design ideas and effective solutions for the deep removal of Mn(II) under acidic conditions and the mitigation mechanism of interface passivation.
[0005] In summary, there is an urgent need in this field to develop a composite mineral material and its preparation method that can efficiently and deeply remove Mn(II) from acidic mine wastewater, effectively alleviate mineral surface passivation, and ensure good environmental stability of manganese-containing sludge, so as to fill the gap in existing technology and meet practical engineering needs. Summary of the Invention
[0006] To address the aforementioned problems, this invention provides a composite mineral material for manganese removal from acidic mine wastewater and its preparation method. In this invention, calcite and forsterite are mixed in a specific ratio and then co-milled and activated using a planetary ball mill. By controlling the specific mechanical energy input within a specific range, and utilizing the significant hardness difference between calcite and forsterite, the hard forsterite abrades the surface of the calcite during co-milling, promoting the exposure of the newly formed reaction surface of the calcite and its structural disorder, while simultaneously constructing a heterogeneous interface with close contact between calcite and forsterite at the nanoscale.
[0007] This heterogeneous interface provides spatially dispersed nucleation sites for Mn(II), allowing manganese-containing precipitates to be discretely distributed across different mineral surfaces and interface regions. This avoids the surface passivation problem caused by the concentrated deposition of Mn(II) precipitates on a limited surface, which gradually forms a continuous and dense capping layer, as seen in single calcite systems. Simultaneously, the dissolution of calcite releases Ca... 2+ and CO3 2- H+ consumption for dissolution of magnesium olivine + Increasing the local pH, together with the other two, creates a chemical microenvironment conducive to Mn(II) fixation, enabling Mn(II) to be fixed through multiple pathways such as carbonate precipitation, hydroxide precipitation, and a small amount of oxidation transformation.
[0008] The composite material prepared by this invention can achieve a removal rate of over 92% for Mn(II) under acidic conditions with an initial pH of 2.5 to 4.0. The residual content in the manganese-containing sludge after treatment is not less than 50%, and the Mn leaching rate does not exceed 3% within the pH range of 2 to 8. It has good environmental stability, low raw material cost, and simple preparation process, making it suitable for use as a deep manganese removal unit in the later stage of combined treatment processes for acidic mine wastewater.
[0009] In a first aspect, the present invention provides a method for preparing a composite mineral material for manganese removal from acidic mine wastewater, comprising the following steps: Mix calcite and forsterite and place them in a ball mill jar; Planetary ball milling was used for co-milling activation, and the ball milling process parameters satisfied the following relationship:
[0010] in, Specific mechanical energy input, expressed in kJ / g; This is a device constant, ranging from 0.8 to 1.2. The ball mill rotation speed is expressed in rpm. The ball milling time is expressed in minutes. The ratio of ball material to mass; The constant is taken as 54; and the range of E is 300~800kJ / g; After ball milling, the solid product is collected to obtain the composite mineral material.
[0011] During the co-milling activation process, due to the significant difference in hardness between calcite (Mohs hardness approximately 3) and forsterite (Mohs hardness approximately 6.5-7), the softer calcite preferentially undergoes crushing and surface wear, while the harder forsterite, under the impact and shearing force of the milling media, produces continuous micro-abrasion on the surface of calcite particles. This causes calcite to continuously expose fresh cleavage planes and active sites, while simultaneously causing lattice distortion and structural disorder, significantly enhancing reactivity. Specific mechanical energy input E is the key process parameter controlling this process: when E is too low (e.g., below 30 kJ / g), the mechanical force is insufficient to effectively drive the abrasion and interfacial bonding between the two minerals, resulting in inadequate calcite activation; when E is too high (e.g., exceeding 800 kJ / g), the minerals are excessively crushed or even amorphized, which weakens the material's reactivity and structural stability. Within the preferred E value range, calcite and forsterite are not only uniformly mixed at the particle scale, but also form a closely contacted heterogeneous interface at the nanoscale. The lattice mismatch and structural distortion at this interface create a rich reactive region, providing a structural basis for the subsequent fixation of Mn(II) in acidic mine wastewater.
[0012] Furthermore, the mass ratio of calcite to forsterite is 1:0.5 to 1:2, with a preferred mass ratio of 1:1.
[0013] Furthermore, the ball milling speed is 500~700 rpm, preferably 600 rpm; the ball milling time is 30~90 min, preferably 60 min; and the ball-to-material mass ratio is (30~70):2, preferably 54:2.
[0014] Secondly, the present invention provides a composite mineral material for removing manganese from acidic mine wastewater.
[0015] Thirdly, the present invention provides a method for removing manganese from acidic mine wastewater, wherein a composite mineral material for removing manganese from acidic mine wastewater is added to the acidic mine wastewater, the dosage is controlled at 0.1~2.0 g / L, and after stirring and reaction, solid-liquid separation is completed to achieve manganese removal.
[0016] Furthermore, the manganese removal rate (%) and initial pH ( ), initial Mn(II) concentration ( (mg / L), dosage ( The following relationship is satisfied for (g / L), where A=2.5~4.0, B=40~80, and C=2.0~4.0.
[0017]
[0018] Furthermore, the reaction time is 1 to 3 hours.
[0019] In summary, the present invention has at least one of the following beneficial technical effects: 1. This invention achieves a removal rate of over 79% to 92% for Mn(II) under acidic conditions (initial pH 2.0 to 4.0) through co-milling and activation of calcite and forsterite, with a dosage of only 0.1 to 2.0 g / L and a reaction time of 1 to 3 hours. Compared with existing technologies that use ball milling of calcite alone or simple physical mixtures, the removal rate is increased by 1.7 to 4.0 times. It is also suitable for the later-stage deep manganese removal unit in combined treatment processes for acidic mine wastewater, and has good engineering adaptability.
[0020] 2. This invention utilizes the significant hardness difference between calcite and forsterite. Through the abrasive effect of forsterite on the calcite surface during co-milling, a calcite-forsterite heterogeneous interface with close contact is constructed at the nanoscale. This heterogeneous interface provides spatially dispersed nucleation sites for Mn(II), allowing manganese-containing precipitates to be discretely distributed on different mineral surfaces and interface regions. This avoids the surface passivation problem caused by the concentrated deposition of Mn(II) precipitates on a limited surface in traditional single calcite systems, which results in a continuous and dense capping layer. XPS analysis shows that Mn(II) is the predominant form in the co-milled mineral system of this invention after reaction, while the proportion of Mn(III) / Mn(IV) oxides in the single calcite system is as high as approximately 67%. This confirms that this invention effectively inhibits the accumulation of high-valence manganese oxides that lead to passivation, thereby maintaining the continuous reactivity of the material.
[0021] 3. In the manganese-containing sludge produced after the treatment by this invention, the proportion of residual manganese is ≥50% of the total manganese, the proportion of reducible manganese is ≤30%, and the leaching rate of Mn(II) is ≤3% in a wide range of pH=2~8, which is much lower than the leaching level of conventional manganese-containing waste residue. This indicates that the sludge has good chemical stability in the natural environment, the risk of manganese re-release is low, and the problem of secondary pollution is avoided. The environmental safety is significantly better than that of the prior art. Attached Figure Description
[0022] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the description of the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 The diagram illustrates the ion release and pH changes of different mineral systems provided in the embodiments of this application; wherein... Figure 1 a represents Ca in different mineral systems 2+ Graph showing the change in release amount over time; Figure 1 b represents different mineral systems Ca 2+ Release rate comparison; Figure 1 c represents the change of pH over time during the reaction of different mineral systems; Figure 1 d represents Mg in different mineral systems 2+ Changes in release over time; Figure 2 This application provides a TEM image of co-ground minerals (showing the calcite-magnesium olivine heterostructure interface). Figure 3 The XRD patterns of co-milled minerals and simple mixed minerals provided in the embodiments of this application are shown. Figure 4 This paper presents a comparison chart of Mn(II) removal rates and endpoint pH values for different mineral systems provided in the embodiments of this application. Figure 5 The following diagram illustrates the effect of different dosages on the removal rate of Mn(II) provided in the embodiments of this application. Figure 6 The following diagram illustrates the effect of the initial Mn(II) concentration on the removal rate and adsorption capacity provided in the embodiments of this application; wherein... Figure 6 a is a graph showing the effect of initial Mn(II) concentration on removal rate; Figure 6 b is a graph showing the effect of the initial Mn(II) concentration on the adsorption capacity; Figure 7 The effect of initial pH on Mn(II) removal rate provided in the embodiments of this application is shown in the figure; Figure 8The diagram illustrates the response surface optimization results and verification experimental results provided in the embodiments of this application; wherein... Figure 8 a is the response surface plot of the interaction between the initial Mn(II) concentration and the dosage; Figure 8 b is the response surface plot of the interaction between pH and dosage; Figure 8 c is the response surface plot of the interaction between the initial Mn(II) concentration and the initial pH value; Figure 9 The XRD patterns of the reaction sediment products provided in the embodiments of this application are shown; wherein Figure 9 a shows the XRD patterns of the co-milled composite material before and after the reaction; Figure 9 b is the Mn2p XPS high-resolution spectrum of a single calcite system; Figure 9 c is the Mn2p XPS high-resolution spectrum of the co-milled mineral system; Figure 10 This illustration shows a schematic diagram of the mechanism for Mn(II) removal using a single calcite system and a co-milled mineral system provided in an embodiment of this application; wherein... Figure 10 a represents a single calcite system; Figure 10 b represents a co-milled mineral system; Figure 11 The graph shows the changes in Mn(II) concentration and pH value in the effluent from an actual AMD dynamic column experiment provided in this application embodiment; Figure 12 The leaching concentration and leaching rate of Mn in the sediment under different initial pH conditions provided in the embodiments of this application are shown; wherein Figure 12 a represents the change in Mn concentration in the leachate under different initial pH conditions; Figure 12 b represents the change in Mn leaching rate under different initial pH conditions; Figure 13 This paper shows the BCR morphology distribution diagram of manganese-containing sludge provided in an embodiment of this application; Detailed Implementation The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. Based on the embodiments of the present invention, any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention. Furthermore, all other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of the present invention.
[0024] Specific experimental steps or conditions are not specified in the embodiments; they can be performed according to the conventional experimental steps or conditions described in the prior art. Reagents and other instruments used, unless otherwise specified, are all commercially available conventional reagent products. Furthermore, the accompanying drawings are merely illustrative diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the drawings denote the same or similar parts, and therefore, repeated descriptions of them will be omitted. Some block diagrams shown in the drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0025] Techniques, methods, and devices known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and devices should be considered part of this specification.
[0026] In the description of this invention, it should be understood that the use of terms such as "first" and "second" to define components is merely for the purpose of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore should not be construed as limiting the scope of protection of this invention.
[0027] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0028] To enable those skilled in the art to better understand this application, the following embodiments are provided to illustrate in detail a composite mineral material for manganese removal from acidic mine wastewater and its preparation method.
[0029] Example Example 1: Preparation and characterization of manganese-removing composite mineral materials Raw materials: commercial calcite powder (CaCO3 content ≥99%, 200 mesh) and forsterite powder (Mg2SiO4 content ≥99%, 200 mesh).
[0030] Co-grinding activation: Weigh 1.0 g each of calcite and forsterite (mass ratio 1:1), and place them in a 45 cm³ container. 3 Five zirconia grinding balls (total weight approximately 54 g, ball-to-material mass ratio 54:2) were added to a zirconia ball mill jar. The mixture was ball-milled at 600 rpm for 60 min on a planetary ball mill. After milling, the powder was collected, sealed, dried, and stored to obtain the co-milled composite material (denoted as CC-OL).
[0031] Characterization of ion release capacity: 0.5 g CC-OL was added to 50 mL of deionized water with an initial pH of 3.0, and after stirring for 2 h, the Ca2+ release capacity was measured. 2+ Release amount. Results as follows: Figure 1 As shown, the Ca of CC-OL2+ The release amount reached 132.04 mg / L, while the Ca released by ball-milled calcite (CC-600) alone under the same conditions was significantly lower. 2+ The release rate was only 81.22 mg / L, and CC-OL increased by 62.6% compared with ball-milled calcite alone; the final pH of the reaction increased from the initial 3.0 to over 7.5.
[0032] Microstructure characterization: CC-OL was observed using transmission electron microscopy (TEM). Results are as follows: Figure 2 As shown, calcite (interface spacing d=0.2799 nm, corresponding to the (104) crystal plane) and forsterite (interface spacing d=0.2319 nm, corresponding to the (112) crystal plane) formed a close contact interface at the nanoscale. There were obvious lattice stripe disorder and distortion near the interface, indicating that an effective heterogeneous interface was formed between the two minerals during the co-grinding process.
[0033] Crystal structure characterization: X-ray diffraction (XRD) was used to compare and analyze the co-milled minerals and simple mixed minerals. The results are as follows: Figure 3 As shown, compared with simple mixed minerals, the (104) characteristic diffraction peak of calcite in co-milled minerals is significantly broadened and weakened, and a splitting peak appears near 29.5°, indicating that co-milling leads to changes in the local structural environment of calcite and a significant increase in the degree of disorder in the crystal structure.
[0034] Example 1 successfully prepared a composite mineral material, CC-OL, with high solubility and reactivity by co-milling and activation of calcite and forsterite. Ion release experiments showed that co-milling activation enhanced the CaO content of CC-OL. 2+ The release rate was increased by 62.6% compared to ball-milled calcite alone, and it could neutralize acidic solutions to neutral. TEM and XRD characterization further confirmed that the two minerals formed a closely contacted heterogeneous interface at the nanoscale during co-milling, while the calcite crystal structure underwent disordering, resulting in a significant mechanochemical synergistic activation effect. The excellent solubility and structural characteristics of this material provide a basis for its efficient removal of Mn(II) under acidic conditions.
[0035] Example 2 Comparison of Mn(II) removal performance of different mineral systems The experimental materials in this embodiment include: unactivated calcite (CC-0), unactivated forsterite (OL-0), ball-milled calcite alone (CC-600, 600 rpm, 60 min), ball-milled forsterite alone (OL-600, 600 rpm, 60 min), a simple physical mixture (CC+OL, CC-600 and OL-600 were manually ground and mixed at a ratio of 1:1), and the co-milling composite material provided by this invention (CC-OL, 600 rpm, 60 min, 1:1).
[0036] The initial concentration of Mn(II) was 50 mg / L, the initial pH was 3.0, the dosage of each material was 2.4 g / L, the reaction time was 2 h, and after the reaction was completed, the supernatant was collected to determine the residual Mn(II) concentration and the endpoint pH was recorded. The results are shown in Figure 1.
[0037] Table 1 Comparison of Mn(II) removal performance of different mineral systems
[0038] Table 1 shows that the removal rate of Mn(II) by unactivated calcite and forsterite was only about 10%, with no significant increase in the final pH, indicating that the natural minerals have extremely low dissolution reactivity under acidic conditions and limited manganese removal capacity. After ball milling activation alone, the removal rates of CC-600 and OL-600 increased to 19.8% and 20.1%, respectively, and the final pH rose to 5.5-6.2, indicating that mechanical activation can improve the reactivity of minerals to some extent, but the improvement effect of a single mineral is still not significant. A simple physical mixture of the two minerals after ball milling (CC+OL) increased the removal rate to 46.8%, and the final pH reached 6.5-7.0, indicating that a synergistic effect occurred when the two minerals coexisted, with calcite dissolution providing Ca. 2+ and CO3 2- The removal of Mn(II) was achieved. However, simple physical mixing only mechanically mixes two independently activated minerals, and the lack of close interfacial contact between them limits the synergistic effect.
[0039] In comparison, such as Figure 4 As shown, the removal rate of the co-milled composite material CC-OL reached 79.8%, with the final pH rising to 7.2-7.5. The removal rate was approximately 4.0 times that of CC-600 and 1.7 times that of CC+OL, significantly superior to all control groups. This result indicates that co-milling activation not only achieved uniform mixing of the two minerals, but more importantly, through the abrasive effect of hard forsterite on the calcite surface during co-milling, a tightly contacted heterogeneous interface was constructed at the nanoscale. This fully leveraged the synergistic effect of the two minerals, causing a rapid increase in system pH and continuous Mn(II) precipitation, ultimately achieving highly efficient Mn(II) removal.
[0040] Example 3: Optimization of Co-grinding Process Parameters To determine the optimal co-milling activation process conditions, this embodiment uses an orthogonal experimental method to systematically optimize the ball milling parameters.
[0041] (1) Orthogonal experimental design The ball-to-material mass ratio (A), ball milling time (B, min), and ball milling speed (C, rpm) were considered as factors, and Ca was used as the basis for analysis. 2+Dissolution rate (mg / L) was used as the evaluation index, and L9 (3) was adopted. 4 A three-factor, three-level orthogonal experiment was conducted using an orthogonal array. The factor and level designs are shown in Table 2.
[0042] Table 2 Factors and Levels in Orthogonal Experiments
[0043] The results of orthogonal experimental range analysis show that each factor affects Ca 2+ The order of influence of dissolution rate is: ball mill speed (C) > ball-to-material ratio (A) > ball milling time (B). The optimal combination of factors is: ball-to-material ratio 54:2, ball milling time 60 min, and ball mill speed 600 rpm.
[0044] Substitute the optimal process parameters into the specific mechanical energy input formula for calculation:
[0045] Set the value to 1.0; =600 rpm; =60 min; =54:2=27; As a constant, we take 54; after calculation, E = 600 kJ / g, that is, the specific mechanical energy input under the optimal process conditions is 600 kJ / g.
[0046] To further investigate the effects of different process parameters on material properties, under the conditions of a fixed ball-to-material ratio of 54:2 and a ball milling time of 60 min, the effect of different ball milling speeds on Ca was examined. 2+ The effects of release amount and Mn(II) removal rate (Mn(II) removal rate test conditions are the same as in Example 2) are shown in Table 3.
[0047] Table 3 Comparison of composite material properties at different ball milling speeds
[0048] As shown in Table 3, with the increase of ball mill speed, Ca 2+ Both the release rate and the removal rate of Mn(II) showed an increasing trend. When the rotational speed was below 500 rpm (corresponding to a specific mechanical energy E of approximately 400 kJ / g), the removal rate of Mn(II) was below 70%, indicating that the mechanical energy input was insufficient to effectively drive the abrasive action between calcite and forsterite and the construction of the heterogeneous interface; when the rotational speed was increased to 600 rpm (E=600 kJ / g), the removal rate of Mn(II) reached 79.8%, and Ca... 2+ The release rate reached 132.04 mg / L, indicating optimal material performance.
[0049] The above results indicate that a suitable specific mechanical energy input (300~800 kJ / g, preferably 450~650 kJ / g) is a key process control parameter to ensure the establishment of an effective heterogeneous interface between calcite and forsterite and to achieve excellent manganese removal performance.
[0050] Example 4: Single-factor experiment and response surface optimization To determine the optimal operating conditions for treating acidic mine wastewater with co-ground composite materials, this embodiment first investigated the influence of each factor on the removal rate of Mn(II) through single-factor experiments, and then optimized the process conditions using response surface methodology.
[0051] (1) The effect of dosage With a fixed initial Mn(II) concentration of 50 mg / L, initial pH of 3.0, and reaction time of 2 h, the effect of composite material dosage in the range of 0.6–4.0 g / L on the Mn(II) removal rate was investigated. The results are as follows: Figure 5 As shown.
[0052] Depend on Figure 5 It can be seen that as the dosage increases from 0.6 g / L to 4.0 g / L, the removal rate of Mn(II) shows a trend of first rapidly increasing and then leveling off. When the dosage increases from 0.6 g / L to 2.4 g / L, the removal rate rapidly increases from 52.3% to 82.8%; when the dosage is further increased to 3.0 g / L, the removal rate slowly increases to 83.1%; after the dosage exceeds 3.0 g / L, the increase in removal rate tends to level off, and further increases in dosage have limited effect on improving the removal rate. This is because increasing the dosage provides more reactive sites and Ca... 2+ / CO3 2- The source promotes the precipitation reaction of Mn(II), but when the dosage is too high, the Ca in the solution... 2+ The concentration is already close to saturation, and excessive solid particles may coat the active surface, thus reducing the utilization efficiency per unit mass of material. Therefore, considering both removal efficiency and material cost, a dosage of 2.4~3.2 g / L is appropriate.
[0053] (2) Effect of initial Mn(II) concentration With a fixed dosage of 2.4 g / L, initial pH of 3.0, and a reaction time of 2 h, the effect of initial Mn(II) concentration in the range of 10–90 mg / L on the removal efficiency was investigated. The results are as follows: Figure 6 As shown.
[0054] Within the range of 10–70 mg / L, the removal rate of Mn(II) gradually increased with increasing initial concentration, reaching a maximum of 87.7% at 70 mg / L; when the initial concentration continued to increase to 90 mg / L, the removal rate decreased slightly. This phenomenon can be attributed to the fact that appropriately increasing the initial Mn(II) concentration is beneficial to promoting the precipitation reaction, but when the concentration is too high, the limited Ca... 2+ and CO3 2- The release amount is insufficient to support the complete precipitation of more Mn(II), and high concentrations of Mn(II) may rapidly form a precipitate coating on the material surface, inhibiting subsequent reactions. On the other hand, the unit loading (adsorption capacity) of Mn(II) continuously increases with the initial concentration, reaching 24.14 mg / g at 90 mg / L, indicating that the material has a high Mn(II) removal capacity.
[0055] (3) Effect of initial pH With a fixed Mn(II) concentration of 70 mg / L, a dosage of 2.4 g / L, and a reaction time of 2 h, the effect of initial pH in the range of 2.0–5.0 on the Mn(II) removal rate was investigated. The results are as follows: Figure 7 As shown.
[0056] Depend on Figure 7 It can be seen that the removal rate of Mn(II) first increases and then decreases with increasing initial pH. When the initial pH increases from 2.0 to 3.0, the removal rate rapidly increases from about 60% to 90.2%; the removal rate reaches its highest at pH=3.0; when the pH continues to rise to 4.0 and 5.0, the removal rate decreases to 82.8% and 88.0%, respectively. The reason for this trend is that when the pH is too low (<3.0), a large amount of H+ in the solution... + It competes with Mn(II) for reaction sites on the mineral surface, while simultaneously inhibiting the dissolution of calcite and the precipitation of Mn(II). At excessively high pH (>4.0), although it favors the precipitation of Mn(II) hydroxides, the excessively high pH weakens the driving force for mineral dissolution, leading to the precipitation of Ca... 2+ and CO3 2- The reduced release rate affects the carbonate precipitation pathway of Mn(II). Therefore, the composite material of this invention is more suitable for the treatment of acidic wastewater with an initial pH of 2.5 to 4.0, with an optimal initial pH of approximately 3.0.
[0057] (4) Response surface optimization Based on the single-factor experiments, a three-factor, three-level response surface optimization experiment was established using a Box-Behnken design (BBD). Initial pH (A), initial Mn(II) concentration (B, mg / L), and dosage (C, g / L) were used as independent variables, and Mn(II) removal rate (Y, %) was used as the response value. Fifteen experiments (including three center-point replicates) were designed for response surface analysis.
[0058] A quadratic polynomial regression model for the removal rate of Mn(II) was established through multivariate regression fitting:
[0059] The model's correlation coefficient R² = 0.9837 indicates a good fit and its applicability for predicting Mn(II) removal rates under different operating conditions. Analysis of variance (ANOVA) results show that the model contains linear terms A, B, and C, and a quadratic term A... 2 B 2 C 2 Both the interaction term AC and AC are significant. p The value <0.05 indicates that the influence of various factors on the removal rate is not a simple linear relationship, and there are interactions between the factors. Using the above model for optimization, the optimal operating conditions were obtained: dosage 3.01 g / L, initial pH = 3.2, and initial Mn(II) concentration 61.35 mg / L. Under these conditions, the model predicted a Mn(II) removal rate of 93.1%. To verify the reliability of the model, three parallel verification experiments were conducted under the above optimal conditions. The actual measured average Mn(II) removal rate was 92.3%, and the relative deviation from the model prediction (93.1%) was less than 1%, confirming that the response surface model has good predictive accuracy. Figure 8 ).
[0060] In summary, through single-factor experiments and response surface methodology optimization, the optimal process conditions for treating acidic manganese-containing wastewater using co-milled composite materials were determined, providing reliable operating parameters for the engineering application of this material.
[0061] Example 5: Removal Mechanism Analysis To reveal the efficient removal mechanism of Mn(II) from acidic mine wastewater by co-grinding composite materials, this embodiment uses X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) to systematically analyze the materials and sludge before and after the reaction, and combines mechanism comparison experiments to clarify the intrinsic mechanism of the co-grinding system in alleviating surface passivation.
[0062] (1) Phase analysis of reaction products XRD was used to identify the phase composition of the sediment product after the reaction of the co-milled composite material. The results are as follows: Figure 9As shown, characteristic diffraction peaks of MnCO3 (PDF#97-019-6041), Mn(OH)2 (PDF#97-005-6152), MnO2 (PDF#97-015-0462), and MnO (PDF#97-065-7312) were clearly detected in the precipitate after the reaction. This indicates that the removal of Mn(II) is not achieved through a single precipitation pathway, but rather through a synergistic process involving multiple pathways such as carbonate precipitation, hydroxide precipitation, and oxidative conversion. The high diffraction peak intensities of MnCO3 and Mn(OH)2 indicate that they are the main products, while the relatively weak peak intensities of MnO2 and MnO suggest they are minor oxidative conversion products. This multi-pathway fixation mechanism helps overcome the limitations of a single precipitation pathway, which is susceptible to pH fluctuations under acidic conditions, enabling the material to maintain stable manganese removal performance under different water quality conditions.
[0063] (2) Analysis of the valence state distribution of manganese To further clarify the differences in the occurrence forms of manganese in different mineral systems, XPS was used to perform peak fitting on the Mn 2p3 / 2 spectra in the sludge after reaction of the single calcite system and the co-ground mineral system. The relative contents of the three valence states of Mn(II), Mn(III), and Mn(IV) were quantitatively analyzed, and the results are shown in Table 4.
[0064] Table 4 Comparison of manganese valence state distribution in different systems
[0065] As shown in Table 4, Mn(II) accounts for as high as 75.5% in the co-milled mineral system, while it accounts for only 33.4% in the single calcite system, forming a stark contrast. In the single calcite system, Mn(III) accounts for as high as 43.9%, and Mn(IV) accounts for 22.7%, with high-valence manganese (Mn(III) + Mn(IV)) accounting for approximately 66.6% in total. This indicates that in the single calcite system, Mn(II) is largely oxidized to high-valence manganese oxides during precipitation; whereas in the co-milled mineral system, Mn(III) accounts for only 4.6%, and high-valence manganese accounts for only about 24.5% in total. This difference indicates that in a single calcite system, the fixation of Mn(II) is dominated by the oxidation pathway, resulting in the formation of a large amount of Mn(III) / Mn(IV) oxides, which accumulate on the calcite surface to form a dense manganese oxide capping layer; while in a co-milled mineral system, the fixation of Mn(II) is dominated by the carbonate / hydroxide precipitation pathway, with Mn(II) existing stably in the sludge in a reduced form.
[0066] High-valence manganese oxides (especially mixed-valence oxides of Mn(III) and Mn(IV)) typically possess high specific surface area and surface reactivity, readily forming continuous, dense deposition layers on mineral surfaces. This hinders the continuous dissolution of CaCO3 and interfacial mass transfer processes. A significantly reduced proportion of high-valence manganese in the co-milled mineral system indicates a lighter accumulation of manganese oxide deposits on the surface, effectively mitigating passivation and enabling the material to maintain sustained reactivity.
[0067] (3) Mechanism schematic analysis In summary, the differences in the removal mechanisms of Mn(II) between the single calcite system and the co-milled mineral system can be summarized as follows: Figure 10 As shown.
[0068] Figure 10 a (single calcite system): Calcite dissolves and slowly releases Ca. 2+ and CO3 2- Mn(II) is deposited concentrated on the limited active sites on the calcite surface, forming a precipitate layer starting with MnCO3. As the reaction proceeds, the surface-adsorbed Mn(II) is gradually oxidized to Mn(III) / Mn(IV) oxides, which together form a continuous and dense capping layer. This capping layer acts as a diffusion barrier, hindering the diffusion of H+ in the solution. + The transport of Mn(II) to the calcite surface inhibits the continuous dissolution of calcite, ultimately leading to a continuous decrease in reactivity and exhibiting typical surface passivation characteristics.
[0069] Figure 10 b (Co-milled mineral system): Calcite and forsterite were co-milled and activated to construct a nanoscale, tightly contacted heterogeneous interface, which provided spatially dispersed nucleation sites for Mn(II); calcite dissolves and releases Ca. 2+ and CO3 2- H+ is consumed by the dissolution of forsterite + and release Mg 2+ and SiO3 2- The two work together to create a chemical microenvironment conducive to Mn(II) fixation; Mn(II) grows independently at multiple dispersed sites, with MnCO3 and Mn(OH)2 as the main precipitates, and a small amount converted into MnO2 and MnO, exhibiting a discrete distribution state, which avoids the formation of a continuous dense capping layer, thereby maintaining the channels for continuous mineral dissolution and interfacial mass transfer, and enabling the material to maintain long-term reactivity.
[0070] In summary, the efficient removal of Mn(II) by the co-grinding composite material is the result of the combined effect of multi-path synergistic fixation and heterogeneous interface passivation mechanism: on the one hand, the co-activation of calcite and forsterite enhances the dissolution reactivity of the minerals, providing a sufficient material basis for the precipitation of Mn(II) carbonates and hydroxides; on the other hand, the heterogeneous interface constructed by co-grinding provides spatially dispersed nucleation sites, effectively inhibiting the formation of a continuous and dense capping layer, enabling the material to maintain continuous and efficient manganese removal performance under acidic conditions.
[0071] Example 6: Verification of Actual Acidic Mine Wastewater Treatment To verify the treatment effect of the composite material of the present invention on actual acidic mine wastewater, static and dynamic treatment experiments were conducted using acidic mine wastewater (AMD) from an abandoned pyrite mine in Xuyong, Sichuan.
[0072] The actual water quality characteristics of AMD were: pH=3.29, Mn(II)=50.48 mg / L, SO4²⁻ - =5142 mg / L, total Fe=18.15 mg / L, Zn=0.32 mg / L. This wastewater exhibits typical characteristics of acidic mine wastewater, with a matrix exhibiting low pH, high sulfate, and the presence of various heavy metal ions, among which the Mn(II) concentration exceeds the manganese limit requirement in the "Integrated Wastewater Discharge Standard" (GB 8978-1996).
[0073] Take 200 mL of the above-mentioned AMD wastewater into a beaker, add the co-ground composite material CC-OL (Example 1) at a dosage of 3.1 g / L, and place it on a magnetic stirrer to stir at 200 rpm for 2 h. After the reaction is completed, let it stand to precipitate, take the supernatant to determine the residual Mn(II) concentration and the endpoint pH.
[0074] The results showed that after 2 hours of reaction, the Mn(II) concentration in the wastewater decreased from the initial 50.48 mg / L to 13.00 mg / L, achieving a removal rate of 74.2%. The effluent pH increased from 3.29 to 7.02, meeting the neutral discharge standard. Furthermore, the treatment effect of the actual wastewater was slightly lower than that of the simulated wastewater (the simulated system in Example 4 of this invention). This is due to the high concentration of SO4 in the actual AMD. 2- (5142 mg / L) and coexisting Fe ions (18.15 mg / L) competitively interfered with the precipitation reaction of Mn(II), SO4 2- Can be used with Ca 2+ The formation of gypsum (CaSO4·2H2O) precipitate consumes some of the Ca. 2+ It may also cover the material surface, and Fe ions preferentially hydrolyze to form hydroxide precipitates during pH increase, competing with Mn(II) for OH-. - and CO3 2-Nevertheless, the removal rate of 74.2% is still significantly better than existing limestone treatment processes (which are typically less than 40%), demonstrating that the present invention still has good manganese removal capabilities under actual complex water quality conditions.
[0075] (2) Dynamic column experiment To further investigate the material's continuous treatment capacity and operational stability, a dynamic circulation column experiment was conducted. CC-OL composite material was packed into an acrylic column with an inner diameter of 2.5 cm and a height of 30 cm, with a packing height of 15 cm. Actual AMD wastewater flowed from top to bottom through the material column at a flow rate of 2 mL / min. The effluent was collected and circulated back to the influent end to simulate continuous operation. Each circulation run lasted 12 hours, for a total of 10 cycles. Samples were periodically taken to measure changes in Mn(II) concentration and pH value in the effluent. The results are as follows: Figure 11 As shown.
[0076] from Figure 11 It can be seen that the Mn(II) concentration in the effluent from the first cycle was 39.78 mg / L, which decreased to 25.61 mg / L in the second cycle. With each cycle, the Mn(II) concentration in the effluent gradually decreased. By the tenth cycle, the Mn(II) concentration in the effluent had dropped to 6.36 mg / L, achieving a cumulative removal rate of 87.4%, and the effluent pH remained stable between 6.60 and 6.81. This is because the material continuously releases Ca during the circulation process. 2+ And consume H + The pH of the system continuously increases; at the same time, the manganese-containing precipitate generated in the early reaction forms a new active interface on the material surface, providing additional nucleation sites for further removal of Mn(II) in subsequent cycles, and promoting the continuous fixation of Mn(II).
[0077] In the dynamic column experiment, the material treated a total of approximately 3.6 L of water and removed approximately 158.8 mg of Mn(II), with a Mn(II) removal capacity per unit mass of material of approximately 7.94 mg / g. Throughout the operation, the effluent pH remained stable between 6.60 and 6.81, and the effluent Mn(II) concentration continuously decreased without showing a trend of declining removal efficiency. This indicates that the composite material of the present invention has good treatment stability and continuous reaction capability under dynamic continuous operation conditions, and can meet the needs of practical engineering applications.
[0078] The above static and dynamic experimental results show that the composite material of the present invention has a stable removal effect on Mn(II) in actual acidic mine wastewater. It can maintain a high removal rate even under complex water quality conditions. Moreover, it can achieve spontaneous neutralization of wastewater pH during the treatment process without the need for external alkali source, showing good engineering application prospects.
[0079] Example 7 Environmental stability evaluation of manganese-containing sludge To assess the stability and potential environmental risks of the manganese-containing sludge generated after treating acidic mine wastewater according to this invention in the natural environment, this embodiment uses pH static leaching experiments and BCR continuous extraction method to analyze the release behavior and speciation of manganese in the sludge.
[0080] The sludge sample was obtained from the static treatment experiment in Example 6 (Sichuan Xuyong AMD, dosage 3.1 g / L, reaction time 2 h). The precipitate after the reaction was collected, centrifuged, washed three times with deionized water, dried at 40°C to constant weight, and ground through a 100-mesh sieve for later use. The manganese content in the sludge was approximately 8.6 wt% (calculated as Mn).
[0081] pH static leaching experiment: To investigate the stability of the sediment under different environmental pH conditions, leaching experiments were conducted according to the "Horizontal Oscillation Method for Leaching Toxicity of Solid Waste" (HJ 557-2010). The initial pH of the leachate was adjusted to 2.0, 4.0, 6.0, and 8.0 with hydrochloric acid and sodium hydroxide solution, respectively. The sediment was mixed with the leachate at a solid-liquid ratio of 1:10 (g / mL), and the mixture was placed in a constant-temperature shaker and shaken at 150 rpm and 25℃ for 18 h. After shaking, the supernatant was centrifuged, and the Mn concentration and endpoint pH were determined. The results are shown in Table 5. Figure 12 As shown.
[0082] Table 5. Leaching behavior of Mn in sediment under different initial pH conditions
[0083] Table 5 shows that under strongly acidic initial conditions (pH=2.0), the Mn leaching concentration was only 12.90 mg / L, with a leaching rate of 2.67%. When the initial pH ≥ 4.0, the leaching concentration dropped to below 5.27 mg / L, with a leaching rate ≤ 1.09%, and the leaching rate was less than 0.5% under near-neutral to weakly alkaline conditions (pH=6.0~8.0). Notably, even under strongly acidic leaching conditions (pH=2.0), the final leaching pH rose to above 5.3, thanks to the buffering effect of the residual calcite and forsterite components in the sludge on the acid, further inhibiting the dissolution of Mn. These results indicate that the manganese-containing sludge has an extremely low Mn leaching rate over a wide pH range, and the risk of Mn release under acid rain or weakly acidic conditions (pH≥4.0) in the natural environment is extremely low, and it will not cause secondary pollution to the surrounding aquatic environment.
[0084] BCR morphological analysis results are as follows: Figure 13As shown, the distribution of Mn speciation in the sediment is as follows: 15% in weakly acid-extractable form, 28% in reducible form, 6% in oxidizable form, and 51% in residual form. The residual form, accounting for 51% of the total Mn, is the dominant form. This portion of Mn is stably bound to the silicate lattice of the minerals and is extremely difficult to release under natural conditions. The reducible form accounts for 28%, which is the second most dominant form. This portion of Mn exists on the surface of iron-manganese oxides in the form of adsorption or co-precipitation, remaining stable under neutral or weakly alkaline conditions and only potentially being released in strongly reducing environments. The weakly acid-extractable form accounts for only 15%, mainly carbonate-bound Mn, which may be released under acidic conditions. However, considering the buffering effect of residual alkaline minerals (calcite and forsterite) in the sediment, the risk of release of this form in the actual environment is low. The oxidizable form accounts for the lowest proportion (6%), indicating that the content of organically bound Mn is extremely low.
[0085] Example 8: Economic Analysis To evaluate the economic feasibility of the engineering application of the technical solution of the present invention, this embodiment conducts a comprehensive analysis from four aspects: raw material cost, preparation cost, wastewater treatment cost, and sludge disposal cost.
[0086] (1) Raw material cost The raw materials used in this invention are natural calcite and forsterite minerals, which are widely available and inexpensive. Based on the average market price of bulk industrial minerals: calcite is approximately 65 yuan / ton, and forsterite is approximately 280 yuan / ton. Calculated using the optimal ratio (mass ratio 1:1), the unit raw material cost of the composite mineral material is 172.5 yuan / ton.
[0087] (2) Preparation cost The preparation process of this invention involves mechanical co-milling activation, with the main energy consumption concentrated in the ball milling process. For engineering scale-up, a combined roller press-stirred mill process is proposed: first, coarse grinding and homogenization are performed using a roller press, followed by fine grinding and co-activation using a stirred mill. This process route is already maturely applied in the mineral processing field, with established experience in equipment matching and process control. Considering energy consumption, equipment depreciation, labor, and maintenance costs, the estimated processing cost is approximately 20-50 RMB / ton (decreasing with increasing production scale). Based on this calculation, the total cost of the composite material is approximately: 172.5 + 20~50 = 192.5~222.5 RMB / ton (equivalent to 0.19~0.22 RMB / kg).
[0088] (3) Wastewater treatment cost The optimal dosage obtained from response surface optimization in Example 4 is 3.01 kg / m³. 3 Based on wastewater calculations, the material cost per unit of wastewater treatment is: 3.01 × 0.19~0.22 ≈ 0.58~0.67 yuan / m³ 3Wastewater. The material cost for treating each cubic meter of acidic mine wastewater should not exceed 0.67 yuan. In actual operation, if the target effluent Mn(II) concentration requirement is relatively lenient (e.g., ≤5 mg / L), the dosage can be appropriately reduced to 2.0~2.5 g / L, and the treatment cost can be further reduced.
[0089] (4) Sludge yield and disposal cost Based on the treatment of acidic mine wastewater with a Mn(II) concentration of approximately 50 mg / L, the material dosage is 3.01 kg / m³. 3 The precipitate after the reaction mainly consists of unreacted mineral residues and manganese-containing precipitates (MnCO3, Mn(OH)2, etc.). The precipitate yield is approximately 3.09 kg / m³. 3 The wastewater, mainly composed of environmentally stable carbonate and silicate minerals, is not classified as hazardous waste (according to the National Hazardous Waste List and hazardous waste identification standards). It can be disposed of as general industrial solid waste or utilized as a resource for building materials. The sludge yield is low, the disposal path is clear, and the overall disposal cost is controllable.
[0090] The raw materials for this invention are widely available, the preparation process is simple, and the processing cost is low, with a comprehensive processing cost of approximately 0.58~0.67 yuan / m³. 3 Wastewater treatment costs are significantly lower than those of neutralization and sedimentation methods (chemical costs + sludge disposal costs are typically 1.5~3.0 yuan / m³). 3 And oxidation precipitation method (reagent + energy cost is usually >3.0 yuan / m³) 3 It has good economic competitiveness and is feasible for engineering promotion.
[0091] In summary, this invention provides a calcite-magnesia olivine co-milling composite material for deep manganese removal from acidic mine wastewater, its preparation method, and its application. This composite material is prepared by co-milling and activating calcite and forsteria olivine at a mass ratio of 1:0.5 to 1:2 using a planetary ball mill. By controlling the specific mechanical energy input E = 300~800 kJ / g, and utilizing the significant hardness difference between calcite and forsteria olivine, the hard forsteria olivine abrades the calcite surface during co-milling, promoting the exposure of the newly formed reaction surface of calcite and structural disorder, while simultaneously constructing a heterogeneous interface with close contact between the two at the nanoscale. This heterogeneous interface provides spatially dispersed nucleation sites for Mn(II), allowing manganese-containing precipitates to be discretely distributed on different mineral surfaces and interface regions, avoiding the surface passivation problem caused by the formation of a continuous dense capping layer due to the concentrated deposition of precipitates on a limited surface in a single calcite system. Simultaneously, the dissolution of calcite releases Ca... 2+ and CO3 2- H+ consumption for dissolution of magnesium olivine +Raising the local pH synergistically creates a chemical microenvironment conducive to Mn(II) fixation, enabling Mn(II) to be fixed through multiple pathways, including carbonate precipitation, hydroxide precipitation, and minor oxidation. Experimental results show that, under initial pH conditions of 2.5–4.0 and dosage of 2.0–4.0 g / L, the composite material achieves a removal rate of over 79%–92% for Mn(II) at concentrations of 30–100 mg / L. The residual content in the treated manganese-containing sludge is ≥50%, and the Mn leaching rate is ≤3% within the pH range of 2–8, demonstrating good environmental stability. The raw material cost is low (approximately 172.5 RMB / ton of composite material), and the treatment cost is approximately 0.58–0.67 RMB / m³. 3 The wastewater treatment efficiency is significantly lower than that of existing processes. This invention effectively solves the technical problem of low manganese removal efficiency caused by surface passivation when treating acidic manganese-containing wastewater with traditional calcite. It provides an efficient, economical, and environmentally friendly solution for the deep removal of Mn(II) from acidic mining wastewater and is suitable for use as a downstream deep manganese removal unit in combined treatment processes for acidic mining wastewater.
[0092] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.
[0093] Although preferred embodiments of the present application have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present application.
[0094] Finally, it should be noted that in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or terminal device that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or terminal device. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or terminal device that includes said element.
[0095] The above provides a detailed description of a composite mineral material for manganese removal from acidic mine wastewater and its preparation method. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A method for preparing a composite mineral material for manganese removal from acidic mine wastewater, characterized in that, Includes the following steps: Mix calcite and forsterite and place them in a ball mill jar; Planetary ball milling was used for co-milling activation, and the ball milling process parameters satisfied the following relationship: in, Specific mechanical energy input, expressed in kJ / g; This is a device constant, ranging from 0.8 to 1.
2. The ball mill rotation speed is expressed in rpm. The ball milling time is expressed in minutes. The ratio of ball material to mass; is a constant, taken as 54; and E ranges from 300 to 800 kJ / g; After ball milling, the solid product is collected to obtain the composite mineral material.
2. The method for preparing a composite mineral material for manganese removal from acidic mine wastewater according to claim 1, characterized in that, The mass ratio of calcite to forsterite is 1:0.5 to 1:
2.
3. The method for preparing a composite mineral material for manganese removal from acidic mine wastewater according to claim 1, characterized in that, The ball milling speed is 500~700 rpm, the ball milling time is 30~90 min, and the ball-to-material mass ratio is (30~70):
2.
4. A composite mineral material prepared by the method for preparing a composite mineral material for removing manganese from acidic mine wastewater as described in any one of claims 1 to 3.
5. A method for removing manganese from acidic mine wastewater, characterized in that, The composite mineral material for manganese removal from acidic mine wastewater as described in claim 4 is added to the acidic mine wastewater, with the addition amount controlled at 0.1~2.0 g / L. After stirring and reacting, solid-liquid separation is completed to achieve manganese removal.
6. The method for removing manganese from acidic mine wastewater according to claim 5, characterized in that, The reaction time is 1 to 3 hours.